Are symptoms of insomnia related to respiratory symptoms? Cross-sectional results from 10 European countries and Australia. Issue 4 (28th April 2020) - Bjornsdottir, Erla; Lindberg, Eva; Benediktsdottir, Bryndis; Gislason, Thorarinn; Garcia Larsen, Vanessa; Franklin, Karl; Jarvis, Debbie; Demoly, Pascal; Perret, Jennifer L; Garcia Aymerich, Judith; Arenas, Sandra Dorado; Heinrich, Joachim; et al.
Abstract : Objectives: To compare the prevalence of different insomnia subtypes among middle-aged adults from Europe and Australia and to explore the cross-sectional relationship between insomnia subtypes, respiratory symptoms and lung function. Design: Cross-sectional population-based, multicentre cohort study. Setting: 23 centres in 10 European countries and Australia. Methods: We included 5800 participants in the third follow-up of the European Community Respiratory Health Survey III (ECRHS III) who answered three questions on insomnia symptoms: difficulties falling asleep (initial insomnia), waking up often during the night (middle insomnia) and waking up early in the morning and not being able to fall back asleep (late insomnia). They also answered questions on smoking, general health and chronic diseases and had the following lung function measurements: forced expiratory volume in 1 s (FEV1 ), forced vital capacity (FVC) and the FEV1 /FVC ratio. Changes in lung function since ECRHS I about 20 years earlier were also analysed. Main outcome measures: Prevalence of insomnia subtypes and relationship to respiratory symptoms and function. Results: Overall, middle insomnia (31.2%) was the most common subtype followed by late insomnia (14.2%) and initial insomnia (11.2%). The highest reported prevalence of middle insomnia was found in Iceland (37.2%) and the lowest in Australia (22.7%), while the prevalence of initial and late insomnia was highest in Spain (16.0% and 19.7%, respectively) and lowest in Denmark (4.6% and 9.2%, respectively). All subtypes of insomnia were associated with significantly higher reported prevalence of respiratory symptoms. Only isolated initial insomnia was associated with lower FEV1, whereas no association was found between insomnia and low FEV1 /FVC ratio or decline in lung function. Conclusion: There is considerable geographical variation in the prevalence of insomnia symptoms. Middle insomnia is most common especially in Iceland. Initial and late insomnia are most common in Spain. All insomnia subtypes are associated with respiratory symptoms, and initial insomnia is also associated with lower FEV1 .